Banat buto a documentary film on the lives of working children in Tayabas city - Jacela, Djacmar Al P.; Regulacion, Christel Ann D. (2016)
The qualitative study produced a documentary film on the lives of working children in Tayabas City, Quezon. Specifically, it sought to feature the different occupations of the working children in Tayabas City; to illustrate the possible risk and danger that the working children may experience; and to determine the government projects being implemented by the municipality of Tayabas. After documenting the everyday lives of the working children and conducting focus interviews, the study revealed that the occupations done by the children are risky, which include selling on the streets, and serving as jeepney conductor. However, during the conduct of the study, the local government does not implement any projects that would protect the working children.
Keywords: Child labor; Documentary films